Selection of proper work duration and rest interval for high-intensity swims of 200 meters
This study repeated the methodology of the previous investigation to determine the most appropriate training sets for 200 m races (61% aerobic, 39% anaerobic energy use). All repetitions were swum at 200 m race pace. Implications: The best set was 12 x 100 m with a 1:2 work:recovery ratio at intended race pace. It is the only exact training set for 200 m racing. Rests greater than 30 sec between each repetition will result in greater use of the anaerobic energy system. Shorter rests of between 10-20 sec result in greater aerobic adaptation, irrespective of the repetition distance or pace.